Analysis of the Technological Evolution of Coffee Production in Brazil - Zanetti, Willian Aparecido Leoti; Marques, Michelle da Silva; Amaral, Ana Maria Santana do; Silva, Adriano Bortolotti da; Barcelos, Jéssica Pigatto de Queiroz; Putti, Fernando Ferrari; Góes, Bruno César (Journal of Agricultural Studies, 2021)
Coffee is one of the most important crops in the Brazilian agricultural sector. In order to position itself as the largest producer and exporter of grains, since to maintain levels, the sector has been associating and introducing concepts of new technologies in the field, processing, as well as in the introduction of increasingly modern equipment. The objective of this work was to verify if the increase in technology provides an increase in production and productivity. Thus, its development started based on data collections from the National Institute of Industrial Property (INPI) in relation to the evolution of new technologies in the Brazilian coffee sector, raising information on patent deposits carried out between the years 1977 and 2017. to collect and classify according to the classification of the IPC (International Classification of Patents), separating according to its technological level and in its area of operation (field, processing and industrial equipment). Performed from the data survey, a verification by the Pearson correlation between the variables. Observing that even with the reduction of areas destined to the culture cultivation, it was possible to identify an increase in production. Evidence that can be associated with the development and application of efficient management, implementation and structuring of technological concepts. In addition to the acceptance of the insertion of new tools and the qualification of labor by the producers, given the need to ensure productive values and guarantee a quality product for the final consumer.